PEMBANGUNAN DAN PENGEMBANGAN SANGGAR KESENIAN NENEK BINI DESA PENGADANGAN - Doyan, Aris; Faizin, Ruhil; Daeng, Ade Claudia Asnan; Ubadah, Lazizatul; Laksari, Zarina Oktavia Dwi; Herdina, Awidya; Ahadusifa, Sarairina; Safitri, Tina Alfiana; Saputra, Lalu Rizki Aldi; Pandu, Anggir; Suhadi, M. Robi Agus (Jurnal Wicara, 2023)
The University of Mataram real work program has one of the work programs, namely it is a great hope for the Pengadangan Village government to be able to build and redevelop the Grandma Bini art studio. The benefits of having a grandmother's art studio are 1). become a forum for developing community interests and talents and preserving the arts and culture of the Pengadangan Village 2). Uniting the existing arts in Pengadangan Village under the same auspices. The construction and development of the grandmother's art studio began with various stages, namely (a) discussions, (b) deliberations, (c) art performances and inauguration of the management. It was agreed regarding the structure of the grand grandmother's art studio which had been formed and designed in such a way by hearing input from various parties. After it was officially agreed, we asked the village head to issue a decree regarding the management of the grandmother's art studio. After the decree from the head of the village of Pengadangan regarding the management structure of the studio, we formed a management structure in the form of a banner that was framed so that later it could be displayed at the village office of Pengadangan. We handed over the management banner on the night of the art performance as a symbol of success in the construction and development of the grandma's art studio. at the same time officially inaugurated by the head of the village of Pengadangan, the chairperson and board member of the arts studio, the grandmother's wife in 2023-2026. The activity of building the grandma bini art studio in Pengadangan village is a form of concern for the arts in the village of Pengadangan, the construction and development of the grandma bini art studio also aims to become a forum for developing community interest and talent and preserving the art and culture of the village of Pengadangan and uniting the arts in the village shelter under the same shade.